Vegetation-Based Assessment of Forage Potential in Cattle–Oil Palm Integrated Farming Systems - Ali, Muhammad Irvan; Purnama, Itang; Hidayatulloh, Rifqi; Atmaja, Baluh Medyabrata; Hutabarat, Amelia Lulu Rosalin; Lestari, Wenni Meika; Safitri, Alief Rahmania; Bakti, Makmur Batara (UNIVERSITAS ISLAM LAMONGAN, 2025)
Integrated cattle–oil palm farming systems (SISKA) have been widely promoted in Indonesia, yet quantitative information on the forage potential of plantation understory vegetation remains limited and site-specific. This study assessed the composition, dominance structure and dry-matter (DM) attributes of understory vegetation in smallholder oil palm plantations (<10 years old) managed under a cattle–oil palm integration scheme in Tanah Laut Regency, South Kalimantan, Indonesia. Vegetation was sampled using twenty 1 × 1 m quadrats per site. For each species, relative density (RD), relative frequency (RF) and a simplified Importance Value Index (IVI = RD + RF) were calculated. Palatability was confirmed by direct observation of cattle intake, and DM content was determined by oven-drying herbage samples to constant weight. A total of 12 species from 7 families were recorded, consisting of grasses (Poaceae), sedges (Cyperaceae), legumes (Fabaceae) and broad-leaved forbs. The understory was strongly dominated by grasses, with Axonopus compressus showing the highest RD (60.36%), RF (16.67%) and IVI (77.03), and a relatively high DM content (33.51%), making it the keystone species in the ground layer. Almost all species (11 of 12; 92%) were classified as palatable to cattle, while only Peperomia pellucida was rejected and contributed negligibly to DM due to its low abundance and very low DM percentage (5.78%). The coexistence of productive grasses, nitrogen-fixing legumes and various forbs indicates a moderately diverse understory community that can provide a continuous, though heterogeneous, forage supply. These findings provide a site-specific, vegetation-based baseline for estimating forage DM potential and designing grazing strategies in SISKA systems, contributing to more productive and sustainable cattle–oil palm integration in Indonesia.